SOCIODEMOGRAPHIC AND CLINICAL PROFILE OF FAMILIES AND INDIVIDUALS WITH AUTISM SPECTRUM DISORDER: PERFIL SOCIODEMOGRÁFICO E CLÍNICO DE FAMÍLIAS E INDIVÍDUOS COM TRANSTORNO DO ESPECTRO AUTISTA - Gomes da Silva Rocha, Joelma; Mabely Azevedo Soares de Oliveira, Karine; Guilherme Dieb Gomes, Victor; Ruama Filgueira de Souza, Ingrid; Coringa de Lemos, Gustavo; Marques Medeiros e Silva, Jaíza (Revista de Ciências da Saúde Nova Esperança, 2024)
Autism Spectrum Disorder (ASD) imposes limitations on individuals and their families, making it necessary to understand these realities to design effective interventions. Therefore, this study aimed to survey the sociodemographic and clinical data of families and individuals with ASD in Mossoró-RN. It is characterized as a descriptive, cross-sectional, and quantitative study, through an active search on social networks and using Google Forms. After the participants had given their consent, a form was used to gather data on the socio-economic and clinical situation of the families. The target population was families with individuals diagnosed with ASD and living in Mossoró - RN. The sample was by convenience, totaling 35 individuals with ASD. Among these, 80% were male, aged between 2 and 19, and the predominant races were white and brown (45.7% each). The most common professional at the time of diagnosis was the neuropediatrician (71.4%), and the most common feeling at this time was fear (34.3%). The diagnosis was received at a late stage by the majority (42.9%), and 25.7% felt satisfied with having received it. About being monitored by health professionals, the majority reported having been (97.1%); however, this monitoring is minimally provided by the Brazilian Unified Health System (SUS) (20%). The most frequently cited day-to-day difficulties were food restrictions (65.7%) and communication (62.9%). Concerning the caregivers’ data, there was a prevalence of females (97.1%), with an age range from 23 to 53 years, married (65.7%), with a high school education (40%), and who did not work (54.3%), with a monthly income of one minimum wage (40%). The urban area prevailed as their home (97.1%). Based on these results, it was possible to identify a profile of individuals and families with ASD in the city of Mossoró, highlighting the need for more targeted public policies and assistance.